2007
DOI: 10.1111/j.1439-0531.2006.00759.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterospecific Nuclear‐transferred Embryos Derived from Equine Fibroblast Cells and Enucleated Bovine Oocytes

Abstract: This study was conducted to reconstruct heterogeneous embryos using equine skin fibroblast cells as donor karyoplasts and the bovine oocytes as recipient cytoplast for investigating the reprogramming of equine somatic cell nuclear in bovine oocyte cytoplasm and the developmental potential of the reconstructed embryos. Adult horse skin fibroblast cells serum-starved were used as donor somatic cells. Bovine oocytes matured in vitro were employed as recipient cytoplasts. The fusion of fibroblast cells into recipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
(18 reference statements)
1
7
0
1
Order By: Relevance
“…Alternatively, not every species has been able to develop to the blastocyst stage when reconstructed with bovine oocytes; it has been reported that cloned mouse [38], equine [39] and domestic cat [22] embryos derived from fibroblasts arrested their development at the eight-cell stage, which is similar to this study. In addition, rabbit oocytes were able to the dedifferentiate somatic cell nuclei of several species, especially cloned intergeneric domestic cats [26].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Alternatively, not every species has been able to develop to the blastocyst stage when reconstructed with bovine oocytes; it has been reported that cloned mouse [38], equine [39] and domestic cat [22] embryos derived from fibroblasts arrested their development at the eight-cell stage, which is similar to this study. In addition, rabbit oocytes were able to the dedifferentiate somatic cell nuclei of several species, especially cloned intergeneric domestic cats [26].…”
Section: Discussionsupporting
confidence: 81%
“…While African wildcat, sand cat and DC are the same genus (Felis), MC belongs to a different genus (Pardofelis), and it can be suggested that the taxonomic distance between the donor and recipient species might be too far, resulting in the DCo not being able to support the development of the NT embryos [40]. Although the use of oocytes from a different genus as recipient cytoplasts in intergeneric NT seems to be efficient for a few mitotic divisions of the resultant cloned embryos, this combination of donor and recipient cells might not lead to the complete nuclear-cytoplasmic events needed for development of cloned embryos, since heteroplasmy or mitochondrial incompatibilities might occur at the time of genomic activation [14,18,26,38,39]. Furthermore, our recent study showed that MCf + DCo intergeneric SCNT resulted in abnormal transcriptional levels of Oct-4, DNMTs, HAT1 and HDAC1 genes, which might be involved in the low developmental potential of these reconstructed embryos [41].…”
Section: Discussionmentioning
confidence: 99%
“…They found that only 17% (8/48) of the equine iSCNT embryos could develop to the four-to eight-cell stage, and none of them could develop to the blastocyst stage, while 15% (10/68) of the bovine PA embryos (control group) reached the blastocyst stage. These reports [11,12,37,40,41] suggest that the iSCNT The cell numbers of the monkey iSCNT embryos from each treatment were significantly different from those of the bovine PA and bovine SCNT embryos (P≤0.01); however, the bovine SCNT and bovine PA embryos (Tr 5 and Tr 6) were not significantly different (P≥0.05).…”
Section: Discussionmentioning
confidence: 84%
“…In our study, the monkey iSCNT embryos could not develop beyond the eight-cell stage, which was consistent with previous reports concerning iSCNT mouse [37,41], dog [42] and camel [11] embryos using bovine [37,41,42] and ovine [11] enucleated oocytes as the recipient cytoplasm. Zhou et al [12] have investigated reprogramming of the equine somatic cell nucleus after injection into bovine enucleated oocyte cytoplasm and the developmental potential of the reconstructed embryos. They found that only 17% (8/48) of the equine iSCNT embryos could develop to the four-to eight-cell stage, and none of them could develop to the blastocyst stage, while 15% (10/68) of the bovine PA embryos (control group) reached the blastocyst stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation